Transplantation to study satellite cell heterogeneity in skeletal muscle - Hekmatnejad, Bahareh; Rudnicki, Michael A. (Frontiers in Cell and Developmental Biology, 2022)
Skeletal muscle has a remarkable capacity to regenerate throughout life, which is mediated by its resident muscle stem cells, also called satellite cells. Satellite cells, located periphery to the muscle fibers and underneath the basal lamina, are an indispensable cellular source for muscle regeneration. Satellite cell transplantation into regenerating muscle contributes robustly to muscle repair, thereby indicating that satellite cells indeed function as adult muscle stem cells. Moreover, satellite cells are a heterogenous population in adult tissue, with subpopulations that can be distinguished based on gene expression, cell-cycle progression, ability to self-renew, and bi-potential ability. Transplantation assays provide a powerful tool to better understand satellite cell function in vivo enabling the separation of functionally distinct satellite cell subpopulations. In this review, we focus on transplantation strategies to explore satellite cells’ functional heterogeneity, approaches targeting the recipient tissue to improve transplantation efficiency, and common strategies to monitor the behaviour of the transplanted cells. Lastly, we discuss some recent approaches to overcome challenges to enhance the transplantation potential of muscle stem cells.